The effect of multigrid parameters in a 3D heat diffusion equation - Oliveira, Fabiane de; Franco, Sebastiao Romero; Villela Pinto, Marcio (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this paper is to reduce the necessary CPU time to solve the three-dimensional heat diffusion equation using Dirichlet boundary conditions. The finite difference method (FDM) is used to discretize the differential equations with a second-order accuracy central difference scheme (CDS).
Keywords: multigrid; finite difference; Poisson 3D; solvers; parameters